ROLE OF FUNDUS AUTOFLUORESCENCE IN THE MANAGEMENT OF AGE-RELATED MACULAR DEGENERATION (The Research of Medical Science Review, 2025)
Objective: To evaluate the usefulness of Fundus Autofluorescence (FAF) in the detection and management of Geographic Atrophy (GA) in Age-Related Macular Degeneration (AMD), and compare its diagnostic accuracy with Spectral-Domain Optical Coherence Tomography (SD-OCT) with the reference standard of Color Fundus Photography (CFP).Methods: This cross-sectional observational study included 40 patients (65–80 years old) with clinically suspected dry AMD. CFP, FAF imaging, and SD-OCT were performed in all patients. GA presence or absence was recorded for all the imaging modalities. Statistical analysis was done using SPSS version 25, and chi-square and t-tests were applied as and where required. The statistical significance level was considered p < 0.05.Results: The age of the patients was 71.0 ± 5.5 years on average. GA was seen in 28 eyes (70%) on CFP, 27 eyes (67.5%) on FAF, and 29 eyes (72.5%) on SD-OCT. SD-OCT was most sensitive in detecting GA (p = 0.007), followed by FAF (p = 0.021), both of which had significant agreement with CFP. FAF and SD-OCT findings had a high correlation (r = 0.84, p < 0.001). GA presence was highly associated with advancing age (p = 0.0003), but not with gender.Conclusion: SD-OCT and FAF are both valuable imaging modalities for GA detection in AMD, with a little more sensitivity when using SD-OCT. FAF for functional information about RPE health is crucial, while SD-OCT for visualization of structure in high detail. Combined, these modalities have enhanced diagnostic accuracy and enable early detection, monitoring, and treatment of AMD progression.